Desain Kemasan Ritel Untuk Buah Alpukat Berlabel Indikator Kematangan - Sari, Novita; Darmawati, Emmy; Ahmad, Usman (Jurnal Keteknikan Pertanian, 2022)
The level ripeness of the avocado was not so easy to know because it not marked with change in color. Consumers generally squeeze the fruit to ensure the level of maturity, therefore a ripe indicator label is needed so that the fruit is not damaged due to frequent pressure. The purpose of this research was to design avocado retail packaging which is equipped with an indicator of fruit maturity. The research was carried out in the following stages: preparation of avocados, production of color indicator matrices made from KMnO4 and Molybdate, selection of retail packaging for 2 pieces per package, application of indicator labels on packaging, storage at room temperature (T1) and low temperature (T2). The packaging is given perforation (P1) and without perforation (P2). The parameters measured were respiration rate, color change of indicator label, hardness and TDS (Total Dissolved Solids) of avocado. The packaging was designed for two avocados weighing 0.5 kg per pack. The packaging material was made of mica plastic measuring 14 x 9 x 6 cm, given perforations of 4 pieces with a diameter of 0,8 mm. the packaging surface area was 528 cm2. The volume of packaging was 756 ml and the average volume of fruit was 553,18 ml and volume of free was 202,82 ml (all sample). The indicator label measuring 2 x 1 cm was placed in the packaging lid. Ethylene produced by avocado could change the color of the indicator label on the packaging. Packaging perforations made the color change of the indicator label more noticeable. On the packaging without perforation there was moisture retained on the indicator label making the label wet and torn. The changes in the oHue value of the indicator label were more correlated (with the change in hardness (r = -0,42) than the value of the TPT (r = 0,071). At low storage temperatures (13±2°C), the correlation of oHue value with hardness was very low (r = 0,059). From these results, it was recommended that the application of avocado ripeness indicator labels should be used at room temperature storage with perforated packaging.torage with perforated packaging.